Regional Differences in Overeducation - Signe Jauhiainen (European Regional Science Association (ERSA), 2006)
This paper focuses on overeducation from the regional perspective. The supply of highly educated workers has increased since late 20th century but the demand has not necessarily increased equivalently. This mismatch might create problems at the labour market, for example unemployment and overeducation. Individuals are not totally mobile and prefer to search for a job near their residential location. If accessible jobs do not correspond to the educational level of the job seeker, one may have to accept a job below his or her educational level. Spatial mobility of workers, migration and commuting, can reduce the spatial mismatch. Spatial mismatch between jobs and workers has been noticed in several studies (see e.g. Büchel & van Ham 2003). The aim of this paper is to find out whether there are regional differences in the proportion of overeducated labour force. Finnish micro level data are used in the analysis. The sample consists of 149 908 individuals who were employed in 2000. Overeducated workers are identified with a statistical measure.
Keywords: 330